Etiología de la enfermedad diarreica aguda en pacientes pediátricos de Latinoamérica: revisión sistemática - León Salinas, Esthéfanny Anahí (2024)
Acute diarrhoeal disease (ADD) is known by the increase in the number of bowel movements in frequency and quantity, it is mainly characterised by the decreased stool consistency and because it lasts no more than 14 days, it is caused by various bacterial, viral and parasitic organisms. This paper aims to identify the prevalence of acute diarrhoeal diseases in Latin American paediatric patients, to classify the most common types of acute diarrhoeal diseases in Latin American paediatric patients, and to identify the existing risk factors for the development of acute diarrhoeal diseases in Latin American paediatric patients. A systematic review was performed, for which we obtained information from the following sources: PubMed, Scielo, Lilacs, considering only the paediatric patients suffering from ADE in Latin America in the last 10 years. The following results were obtained; the prevalence of ADEs applying the median was of 63.86%. The most predominant etiological agents were bacteria Escherichia coli with 49.08%, then the parasites Entamoeba histolytica 15.77%, and finally the viruses, with the Rotavirus 16.18% existing in greater quantity. The risk factors were classified into environmental and social, among which we have the rural origin 76.10%, related to lifestyle and hygiene there is the type of breastfeeding 71.57% and in others maternal schooling was obtained 85%. Therefore, it is concluded that the prevalence of acute diarrheal diseases in paediatric patients in Latin America is significantly high, the highest numbers are more frequent in countries with a low socioeconomic status. The classification of the predominant types in acute diarrheal diseases was mainly conformed by bacteria, followed by parasites and in few cases by viruses. And the existing risk factors for the development of ADEs were environmental and social, lifestyle and hygiene, among others